The Influence of Covid-19 and Foreign Investment on Regency/City Grdp in Riau Province in 2017-2021 - Nasution, Hannisa Sasilia (Politeknik Negeri Bengkalis, 2023)
This study aims to analyze the effect of Covid-19 and Foreign Investment on the value of the Regency/City Gross Regional Domestic Product (GRDP) in Riau Province in 2017-2021. This study uses quantitative research methods with panel data analysis methods and processed using Eviews 10. The dependent variable is Gross Regional Domestic Product in 11 Regency/Cities in Riau Province. The independent variables in this study are the value of Foreign Investment and Covid-19 using dummy numbers. The results of this study indicate that foreign investment has a positive but not significant effect on the GRDP of Regency/city in Riau Province. Meanwhile, the dummy variable of Covid-19 has a positive and significant effect on Regency/City GRDP in Riau Province